The prevalence and predictors of clinical breast cancer screening in Sub-Saharan African countries: a multilevel analysis of Demographic Health Survey - Hailegebireal, Aklilu Habte; Bizuayehu, Habtamu Mellie; Wolde, Biruk Bogale; Tirore, Lire Lemma; Woldegeorgis, Beshada Zerfu; Kassie, Gizachew Ambaw; Asgedom, Yordanos Sisay (Frontiers in Public Health, 2024)
Background Despite a higher rate of breast cancer in sub-Saharan Africa (SSA), efforts to treat the disease through breast cancer screening are suboptimal, resulting in late diagnosis of breast cancer and poor outcomes. Several studies have been conducted in SSA countries about screening uptake, yet they addressed country or sub-country level data and did not consider both individual and beyond-individual factors related to screening. Hence, pooled prevalence as well as multilevel correlates of screening in the region is sparse, which have been addressed by this study using the most recent data among women with SSA. Methods This study was conducted using the Demographic Health Survey data (2013–2022) from six countries, and a total weighted sample of 95,248 women was examined. STATA version 16 was used for the data analysis. Multilevel mixed-effects logistic regression was performed and significant predictors were reported using adjusted odds ratios (aOR) with 95% confidence intervals (95% CI). Results The overall weighted prevalence of clinical breast cancer screening was 14.23% (95% CI: 13.97–14.75), with Namibia and Tanzania having the highest (24.5%) and lowest (5.19%) screening rates, respectively. Higher breast cancer screening uptake was observed among women of advanced age (35–49) [aOR = 1.78; 95% CI: 1.60, 1.98], had higher educational levels [aOR = 1.84; 95% CI: 1.66, 2.03], cohabited [aOR = 1.37; 95% CI: 1.21, 1.55], in the richest wealth quintile [aOR = 2.27; 95% CI: 1.95, 2.64], urban residents [aOR = 1.21; 95%CI: 1.10, 1.33], multiparous [aOR = 1.47; 95% CI: 1.30, 1.68], visited health facilities [aOR = 1.64; 95% CI: 1.52, 1.76], and read newspapers [aOR = 1.78; 95%CI: 1.60, 2.15]. Conclusion The prevalence of clinical breast cancer screening was low (14%). Strengthening awareness campaigns, improving healthcare infrastructure, health education, universal health coverage, and screening program access, with a focus on rural areas, women who lack formal education, and low socioeconomic status, are critical to increasing breast cancer screening rates and equity. Scale-up local and regional collaborations and the involvement of media agencies in the implementation of screening programs, advocacy, dissemination of information, and integration of screening programs with their routine care, such as perinatal care, can boost the screening. The existing health service delivery points also need to focus on integrating breast cancer screening services with routine care such as perinatal care.